2017
DOI: 10.19175/recom.v7i0.1558
|View full text |Cite
|
Sign up to set email alerts
|

Preval�ncia de pediculose de cabe�a em crian�as inseridas em centros municipais de educa��o infantil

Abstract: Objetivo: O estudo objetivou identificar a preval�ncia da pediculose de cabe�a entre crian�as de 2 a 5 anos inseridas nos Centros Municipais de Educa��o Infantil (CMEI) de Divin�polis, MG. M�todo: O m�todo de estudo utilizado foi o transversal, de base populacional, com amostra de 326 crian�as. Realizou-se inspe��o da cabe�a e aplica��o de question�rio sociodemogr�fico. O modelo multivariado de an�lise estat�stica utilizado foi a Regress�o Linear de Poisson. Resultados: A preval�ncia de pediculose de cabe�a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…The selected studies pointed out that the infestation showed variations in the prevalence rates of parasitosis among men and women. However, in seven studies, females obtained the highest proportions of infected people, in studies conducted in Uberlândia 40,[43][44][45][46] , Belo Horizonte 39 and Divinópolis 42 . Only in one of the studies that evaluated the presence of the parasite in hair samples, positivity was higher for males 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected studies pointed out that the infestation showed variations in the prevalence rates of parasitosis among men and women. However, in seven studies, females obtained the highest proportions of infected people, in studies conducted in Uberlândia 40,[43][44][45][46] , Belo Horizonte 39 and Divinópolis 42 . Only in one of the studies that evaluated the presence of the parasite in hair samples, positivity was higher for males 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies addressed the prevalence of P. humanus capitis infestation in groups, age groups, or only by age. There was a prevalence of parasitosis in children aged 1 to 12 years old 38,40,[42][43][44][45] , although other studies also found the presence of head lice in young people, adults and the elderly population 41,46 . The most prevalent age groups mentioned in this review are justified by the fact that the studies developed in the state focus mainly on places with people of younger age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Destaca-se, portanto, que as ações lúdicas nos processos de ensino e aprendizagem são importantes meios para desenvolver habilidades cognitivas nos estudantes sobre os conteúdos conceituais abordados. A aplicação dos jogos educativos, como o referido neste artigo, é uma forma de contribuição lúdica e de baixo custo para que os estudantes construam seu conhecimento a respeito de distintos conteúdos (JUSTINIANO, et al, 2015;COSTA, et al, 2017;BOGÉA, et al, 2020) Para retirar o piolho da cabeça é preciso usar pente fino e piolhicidas.…”
Section: Considerações Finaisunclassified
“…Além disso, algumas doenças crônicas não transmissíveis (DCNT) que representam problemas de saúde pública de grande magnitude em âmbito nacional como a diabetes mellitus estão sendo objetos de estudos através dos games (COSTA et al, 2017). No estudo de DIEHL et al, (2015) foi utilizado um game "InsuOnLine" com o objetivo de aperfeiçoar a prática profissional sobre a insulina e o diabetes.…”
Section: Meio Digitalunclassified